A process simulation study of CO2 capture by ionic liquids. (March 2017) - Ma, Tao; Wang, Jiexin; Du, Zengzhi; Abdeltawab, Ahmed A.; Al-Enizi, Abdullah M.; Chen, Xiaochun; Yu, Guangren
Highlights: [bmim][BF4 ] and [bmim][PF6 ] are two efficient absorbents for CO2 capture. A new ILs-based CO2 capture process is developed and simulated. Negligible corrosion and solvent loss problems in such a process. Energy consumption in IL-based process is >25% lower than that in MEA-based process. ILs-based CO2 capture process is a very promising alternative technology. Abstract: This study was aimed to simulate a new ionic liquids (ILs)-based CO2 capture process which is useful to capture CO2 from model flue gas, by using two promising CO2 absorbents, 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4 ]) and 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF6 ]). Thermodynamic properties such as vapor pressure, heat capacity and density were modeled. Vapor-liquid equilibrium (VLE) data were calculated by Redlich-Kwong (R-K) equation and NRTL model. The calculated VLE data were in good agreement with the experimental values. This ILs-based CO2 capture process is characterized with few advantages such as there is no issue of water; solvent (ILs) loss is negligible as compared to monoethanolamine (MEA)-based CO2 capture process (e.g., 0.299 g/tCO2 for [bmim][BF4 ] and 0.391 g/tCO2 for [bmim][PF6 ] respectively, while 178 g/tCO2 for MEA); potential corrosion risk is excluded; the energy consumption in [bmim][BF4 ]- and [bmim][PF6 ]-based processes are lowered up to 26.7% and 24.8% respectively than that in MEA-based process. Thus, such an ILs-based CO2 capture process is more competitive than traditional MEA-based CO2 capture process.